2005
DOI: 10.1007/s11199-005-8292-4
|View full text |Cite
|
Sign up to set email alerts
|

Student Evaluations and Gendered Expectations: What We Can't Count Can Hurt Us

Abstract: Does teacher's gender impact students' evaluations? We critically evaluated the research literature and concluded that the form gender bias takes may not be easily detectible by quantitative scales. To explore this possibility, we did a qualitative analysis of the words that 288 college students at two campuses used to describe their best-and worst-ever teachers. Although we found considerable overlap in the ways that students talked about their male and female teachers, we also saw indications that students h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 42 publications
8
97
1
2
Order By: Relevance
“…Students have reported feeling betrayed and deeply disappointed when these expectations are not met (Heinrich, 1995). Female faculty who do not fulfill gendered role expectations are reported to receive hostile responses in student evaluations (Sprague & Massoni, 2005).…”
Section: Faculty Factorsmentioning
confidence: 99%
“…Students have reported feeling betrayed and deeply disappointed when these expectations are not met (Heinrich, 1995). Female faculty who do not fulfill gendered role expectations are reported to receive hostile responses in student evaluations (Sprague & Massoni, 2005).…”
Section: Faculty Factorsmentioning
confidence: 99%
“…It has been previously documented that women are judged more harshly than men in teaching evaluations (Sprague & Massoni 2005); however, the question regarding whether female students are judged by faculty more harshly than male students for academic dishonesty has not been explored. To investigate this, we analyzed gender aspects of academic dishonesty based on data from disciplinary boards of several Swedish universities.…”
Section: Aim and Purposementioning
confidence: 99%
“…Sprague and Massoni ( 2005 ) found that students tend to hold certain gendered expectations for faculty members. For example, female professors are expected to be caring and nurturing, whereas male professors are expected to be funny and energetic.…”
Section: Discussionmentioning
confidence: 99%